Importance of Aberrant Right Subclavian Artery Detection During Second Trimester Ultrasound Examination in Low-Risk Population - Erdal Seker; Hasan Sut; Mustafa Kocar; Coskun Umit; Esra Ozkavukcu; Acar Koc (Gynecology Obstetrics & Reproductive Medicine)
OBJECTIVE: Aberrant right subclavian artery, which is detected in 1-1.5% of the population, is considered an anatomical variant. Aberrant right subclavian artery is usually not symptomatic, but can sometimes lead to dysphagia due to esophageal compression. On the other hand, it has been found that it has accompanied some fetal anomalies in the last two decades. Although aberrant right subclavian artery is seen at a rate of 1-1.5% in normal chromosomal fetuses, it is seen at a rate of 19-36%, especially in fetuses with Down syndrome.